2020
DOI: 10.1016/j.phro.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging on hybrid magnetic resonance linear accelerators: Perspective on technical and clinical validation

Abstract: Many preclinical and clinical observations support that functional magnetic resonance imaging (MRI), such as diffusion weighted (DW) and dynamic contrast enhanced (DCE) MRI, might have a predictive value for radiotherapy. The aim of this review was to assess the current status of quantitative MRI on hybrid MR-Linacs. In a literature research, four publications were identified, investigating technical feasibility, accuracy, repeatability and reproducibility of DW and DCE-MRI in phantoms and first patients. Accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
0
28
0
2
Order By: Relevance
“…Furthermore, first technical studies have shown that MR imaging using the 1.5 T Unity system not only provides excellent anatomic image data 40,41 but also allows for robust and reproducible quantitative imaging techniques, such as diffusion-weighted imaging. [40][41][42][43] Consequently, functional MR data acquired sequentially during MR-guided RT needs to be investigated systematically to pave the way toward future biologically individualized RT of HNC. Next steps include an R-IDEAL stage 2a evaluation of functional imaging integration and feasibility with diffusion-weighted imaging and stage 2a implementation using an ART reduco 14 approach within the prospective phase 2 randomized MR-ADAPTOR trial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, first technical studies have shown that MR imaging using the 1.5 T Unity system not only provides excellent anatomic image data 40,41 but also allows for robust and reproducible quantitative imaging techniques, such as diffusion-weighted imaging. [40][41][42][43] Consequently, functional MR data acquired sequentially during MR-guided RT needs to be investigated systematically to pave the way toward future biologically individualized RT of HNC. Next steps include an R-IDEAL stage 2a evaluation of functional imaging integration and feasibility with diffusion-weighted imaging and stage 2a implementation using an ART reduco 14 approach within the prospective phase 2 randomized MR-ADAPTOR trial.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, interventions steered by functional MR imaging biomarkers seem to be one of the most promising concepts towards personalized, biologically individualized RT. Even though prognostic information using functional MR imaging may also be gathered with state-of-the-art diagnostic MR systems which do not suffer from hardware limitations such as the hybrid MR-linac scanners ( 74 ), biological real-time adaptation such as image biomarker guided dose painting to overcome local tumor radiation resistances can only be realized on hybrid MR-linacs ( 75 ). Biological RT individualization in terms of dose adaptation based on imaging information requires the measurement of quantitative imaging biomarkers ( 76 ).…”
Section: Functional Imagingmentioning
confidence: 99%
“…Models able to provide reliable predictions during the RT course can be of great value to clinicians, allowing timely change of the dose prescription, moving towards dose escalation, or alternative approaches for patients indicated by the model as not-responders, in the perspective of response-based treatment adaptation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%